SEGMENTASI CITRA MRI MENGGUNAKAN DETEKSI TEPI UNTUK IDENTIFIKASI KANKER PAYUDARA - Ervina Farijki; Bambang Krismono Triwijoyo (Universitas Bumigora, 2016)
One type of cancer that is capable identifed using MRI technology is breast cancer. Breast cancer is still the leading cause of death world. therefore early detection of this disease is needed. In identifying breast cancer, a doctor or radiologist analyzing the results of magnetic resonance image that is stored in the format of the Digital Imaging Communication In Medicine (DICOM). It takes skill and experience suffcient for diagnosis is appropriate, and accurate, so it is necessary to create a digital image processing applications by utilizing the process of object segmentation and edge detection to assist the physician or radiologist in identifying breast cancer. MRI image segmentation using edge detection to identifcation of breast cancer using a method stages gryascale change the image format, then the binary image thresholding and edge detection process using the latest Robert operator. Of the 20 tested the input image to produce images with the appearance of the boundary line of each region or object that is visible and there are no edges are cut off, with the average computation time less than one minute.